HASIL BELAJAR KETERAMPILAN MENULIS DESKRIPSI DENGAN MODEL TPW (THINK PAIR WRITE) KELAS X SMAN 12 SURABAYA - Sianes, Yessy (LATERNE, 2017)
Writing in a foreign language is one of the most productive language skills. Students of X-MIA class 3 SMAN 12 Surabaya consider writing as the most difficult skill. Students have difficulties in developing ideas within and learning outcomes of writing students are categorized less. The success of writing skills is determined by several factors, one of which is the model of learning used in learning process. One of the efforts that can be done is to change the more innovative and creative learning model, such as model TPW (Think Pair Write). TPW is one model of cooperative learning. TPW is a model of learning, that is implemented by pairs with emphasis on the process of thinking and writing. So every student will be forced to develop their ideas. If TPW is applied regularly, then the students writing skills will increase. Formulate of the problem in this research is "How is learning outcomes of description writing skills with TPW (Think Pair Write) model in the class X SMAN 12 Surabaya ?". This is a qualitative research. Subject in this research is students of class X MIA-3 SMAN 12 Surabaya with the total number 31 students. The data of this research is obtained of the test result during 4 meetings and documentation as supporting data. The first test result only (6 students) is categorized very good. The second test result  (15 students) is categorized very good. The third test result  (16 students) is categorized very well. The results of the fourth test (21 students) are categorized very good. It is inferential that the TPW (Think Pair Write) can be used a German alternative, especially in the writing skill. Keywords: TPW (Think Pair Write), Writing Skills, Learning Outcomes.